2007
DOI: 10.1186/1471-2180-7-108
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial flora-typing with targeted, chip-based Pyrosequencing

Abstract: Background: The metagenomic analysis of microbial communities holds the potential to improve our understanding of the role of microbes in clinical conditions. Recent, dramatic improvements in DNA sequencing throughput and cost will enable such analyses on individuals. However, such advances in throughput generally come at the cost of shorter read-lengths, limiting the discriminatory power of each read. In particular, classifying the microbial content of samples by sequencing the < 1,600 bp 16S rRNA gene will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(178 citation statements)
references
References 33 publications
5
172
0
1
Order By: Relevance
“…In the same manner, in the past years other researchers have been focusing on other domains for classification purposes. For instance, Sundquist et al [25] favored the domains V1,V2 and V4, Liu et al [26] the domains V2, V3 and V4, and Chakravorty et al [27] the domains V2 and V3.…”
Section: Amplified Genomic Regionsmentioning
confidence: 99%
“…In the same manner, in the past years other researchers have been focusing on other domains for classification purposes. For instance, Sundquist et al [25] favored the domains V1,V2 and V4, Liu et al [26] the domains V2, V3 and V4, and Chakravorty et al [27] the domains V2 and V3.…”
Section: Amplified Genomic Regionsmentioning
confidence: 99%
“…For 16S rRNA gene sequences, accurate phylogenies require from about 800 nt to full sequences and even so provide insufficient information to resolve many phylogenies, particularly for cases of heterogeneous rates and deep branches. Elaborate methods such as in 140) or extension of phylogenetic analysis to the genome scale 185) 160) suggested that reads from variable domains could allow to assign up 80% of them to a genus, but since these estimates were done using a very small subset of sequences these estimates are probably much too high. For example, using sequences from environmental clone libraries of length greater than 300 nt 73) found that nearly all of the taxonomic assignments were spurious, as the best match had a sequence similarity below 96%, and concluded that 79 to 89% of clones could not be assigned to known genera when sequences belonged to poorly defined groups with very few described species.…”
Section: Retrieving Datamentioning
confidence: 99%
“…Finally mass sequencing 30,85,187) or 16S rRNA mass cataloging 72) or even different methods 1,52,188) are appearing. Massive Parallel Sequencing (MPS) 4,56,110) that can presently produce 400,000 reads per run, with lengths averaging 200 to 300 bases per read (more than 20 million bases per 4.5-hour instrument run) now allows to sequence the entire molecule 161) or selectively variable short domains of the 16S rRNA gene 30,33,63,89,93,116,138,151,160,169) seemingly with good accuracy 70) . These short sequences will be referenced as "tags" below in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…As with cult uring, the primary drawbacks of molecular methods include both labor and financial costs. Recently, DNA sequencing has been revolutionized by the introduction of massively parallel sequencing systems, such as 454 pyrosequencing analysis (Margulies et al, 2005;Cristea-Fernstrom et al, 2007;Huse et al, 2007;Liu et al, 2007;Roesch et al, 2007;Sundquist et al, 2007). Pyrosequencing techniques are high-throughput analytical tools that are capable of generating large numbers of DNA reads through a massively parallel sequencing-by-synthesis approach (Margulies et al, 2005).…”
Section: Introductionmentioning
confidence: 99%